Zinc biofortification of hydroponically grown basil: Stress physiological responses and impact on antioxidant secondary metabolites of genotypic variants - Ciriello, Michele; Formisano, Luigi; Kyriacou, Marios; Soteriou, Georgios A.; Graziani, Giulia; De Pascale, Stefania; Rouphael, Youssef (Frontiers in Plant Science, 2022)
Ocimum basilicum L. is an aromatic plant rich in bioactive metabolites beneficial to human health. The agronomic biofortification of basil with Zn could provide a practical and sustainable solution to address Zn deficiency in humans. Our research appraised the effects of biofortification implemented through nutrient solutions of different Zn concentration (12.5, 25.0, 37.5, and 50 µM) on the yield, physiological indices (net CO2 assimilation rate, transpiration, stomatal conductance, and chlorophyll fluorescence), quality, and Zn concentration of basil cultivars ‘Aroma 2’ and ‘Eleonora’ grown in a floating raft system. The ABTS, DPPH, and FRAP antioxidant activities were determined by UV-VIS spectrophotometry, the concentrations of phenolic acids by mass spectrometry using a Q Extractive Orbitrap LC-MS/MS, and tissue Zn concentration by inductively coupled plasma mass spectrometry. Although increasing the concentration of Zn in the nutrient solution significantly reduced the yield, this reduction was less evident in ‘Aroma 2’. However, regardless of cultivar, the use of the maximum dose of Zn (50 µM) increased the concentration of carotenoids, polyphenols, and antioxidant activity on average by 19.76, 14.57, and 33.72%, respectively, compared to the Control. The significant positive correlation between Zn in the nutrient solution and Zn in plant tissues underscores the suitability of basil for soilless biofortification programs.